Consumer Demand in the United States / Second and Enlarged Edition - Houthakker; Taylor J. P (1965)
Introduction, The Economic Background, Problems of Estimation and Projection, Demand Equations for Individual Items of Expenditure, Discussion of the Demand Equations and Projections, An Additive Dynamic Model, Evidence from the 1960-1961 Household Survey, The Dynamics of Total Consumption and Saving, Evaluation, Data Sources, References, Index.